2022
DOI: 10.3389/fpls.2022.955656
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Plants and Species Richness Impact Litter Decomposition in Riparian Zones

Abstract: Natural ecosystems generally include litter decomposition as part of the natural cycle since the material properties and the environment greatly influence the decomposition rate. The invasion of exotic plants alters the species diversity and growth characteristics of plant communities, but its impact on litter decomposition is unknown in the riparian zone. This study examines how invasive plants affect the early stages of litter decomposition and how species richness impacts them. This experiment involved a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 79 publications
2
26
2
Order By: Relevance
“…Similar results have been documented by Arif et al [ 2 ] within the Three Gorges Reservoir, China. In other studies, those indicators have shown different patterns as situations change everywhere [ 14 , 36 , 37 ], which is consistent with the results obtained in the current study. Changes in riparian zones are influenced by geographical locations and stressors [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results have been documented by Arif et al [ 2 ] within the Three Gorges Reservoir, China. In other studies, those indicators have shown different patterns as situations change everywhere [ 14 , 36 , 37 ], which is consistent with the results obtained in the current study. Changes in riparian zones are influenced by geographical locations and stressors [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Various factors influence the dynamics of stressors, and hydro-morphological changes are critical to exacerbating their effects [ 16 , 45 ]. When environmental conditions and land use change, these changes may influence the structure and growth of plant communities [ 36 ]. Nevertheless, the impact on riparian zones can vary according to the location of the transect and the magnitude of stressors [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unique hydrological conditions in the TGR region, the plants in this region have a special growth pattern that is continuously submerged in a cycle that repeats each year ( Chen et al, 2021 ; Li J. J. et al, 2021 ). Consequently, most of the riparian plants could not withstand these huge water level changes and gradually died ( Gul et al, 2022 ; Hu et al, 2022 ), resulting in severe degradation of the ecological environment in the region and, thus, the functional decline of the riparian ecosystem, which seriously jeopardized the operation of the TGR. Therefore, it is important to know how the riparian plant community responds to dam inundation and to restore vegetation within the hydro-fluctuation zone to improve the area’s ecosystem quality and ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…To be sure, this large constructed wetland ecosystem, especially the aquatic environment, will be disturbed by hydrological rhythms. Meanwhile, the plants in the wetland ecosystem play an important role in the nutrient cycle of the TGR area, which can regulate soil nutrient availability as well as the aquatic environment (Ding et al, 2021;Hu et al, 2022;Yuancai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%